Comparison of the Competitiveness for Danish, Dutch, and German Piglet Producers under Consideration of Country-Specific Methods of Piglet Castration with Anesthesia - Mandes Verhaagh (Agriculture)
Pig producers in Europe adopt different production methods for male pig fattening. More than half of the animals are surgically castrated. The different interpretations of animal welfare in different countries lead to market differentiation and economically different production conditions, which do not restrict trade, but economically lead to drastic competitive changes for local producers. While the Netherlands has already implemented surgical castration for the export market, using CO2 narcosis (NL), Denmark and Germany are each introducing their strategies with local anesthesia (DK) and isoflurane anesthesia (DE), respectively. Using typical pig farms from the agri benchmark Pig Network, the additional costs and economic impacts of animal welfare regulations are calculated. In Germany, isoflurane anesthesia increases costs by EUR 28.54 to EUR 49.86 per sow, or EUR 1.93 to EUR 3.81 per male piglet. This corresponds to a cost increase of around 5% per piglet. In Denmark, the costs of local anesthesia with procaine increase more moderately by EUR 3.55 to EUR 5.05 per sow, or around EUR 0.30 per male piglet. The cost increase here is less than 1% per piglet. The additional costs are leading to a loss of competitiveness for Denmark and Germany compared to the Netherlands. However, Germany is also losing profit significantly compared to Denmark. This study highlights that animal welfare regulations can negatively impact the competitiveness of the pig sector. It emphasizes the need for countries to implement such regulations carefully, ensuring that they do not lead to the loss of production or international competitiveness. A balanced approach that supports both animal welfare and economic sustainability is essential.